Frequency of Hyperuricemia in Patients with Psoriasis - Hussain, Muhammad Zahid; Ullah, Irfan; Khan, Mehran; Khan, Najeeb Ullah; Iqbal, Khalid; Ali, Farhad (Biological and Clinical Sciences Research Journal, 2025)
Psoriasis is a chronic inflammatory skin disorder associated with systemic comorbidities, including metabolic syndrome and cardiovascular diseases. Hyperuricemia, characterized by elevated serum uric acid levels, has been implicated in systemic inflammation and metabolic dysfunction. However, its prevalence and association with psoriasis remain underexplored. Objective: To determine the frequency of hyperuricemia in patients with psoriasis. Methodology: A descriptive cross-sectional study was conducted at Khyber Teaching Hospital, Peshawar for six months from 22 June 2022 to 22 December 2022. One hundred twenty-one psoriasis patients, aged 12 to 70 years, were selected through a consecutive non-probability sampling method. Individuals with pulmonary disorders, chronic kidney disease, or those receiving medications that reduce uric acid levels were excluded from the study. The frequency of hyperuricemia was assessed in all patients. Results: The study found that 21.5% of psoriasis patients had hyperuricemia. The mean age of participants was 40.31 ± 12.82 years, and the mean disease duration was 5.82 ± 2.59 years. There was a significant association between disease duration and hyperuricemia (p = 0.044). However, no significant correlations were found between hyperuricemia and age, gender, or BMI (p > 0.05). Conclusion: The study concluded that hyperuricemia is prevalent among psoriasis patients, particularly those with a longer disease duration. Routine screening for hyperuricemia in psoriatic patients is recommended to prevent associated comorbidities, such as cardiovascular disease and metabolic syndrome.